Peningkatan Literasi Digital dan Bahasa Inggris bagi Generasi Muda Desa Kejawang melalui Seminar “AI & English: Kunci Sukses Generasi Masa Depan” - Akhmad Fadjeri; Syafina Hikmah Rahmani; Unggul Priyo Prasojo; Riska Dwi Handayani; Tri Anggoro; Taufik Hidayat; Rissa Filyang; Anisa Dwi Nurchayati; Aulia Rahmawati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Kejawang Village faces a lack of English language skills and a shortage of competent teachers. One option for addressing this issue is through community service programs and the use of technology.This Independent Community Service Program (KKN) aimed to enhance the understanding of the young generation in Kejawang Village regarding the importance of digital literacy and English proficiency in the globalization era. The method used was an interactive seminar titled